Trichloromethane dechlorination by a novel Dehalobacter sp. strain 8M reveals a third contrasting C and Cl isotope fractionation pattern within this genus - Soder-Walz, Jesica M; Torrentó, Clara; Algora, Camelia; Wasmund, Kenneth; Cortés, Pilar; Soler, Albert; Vicent, Teresa; Rosell, Mònica; Marco-Urrea, Ernest (The Science of the total environment, 2022)
Trichloromethane (TCM) is a pollutant frequently detected in contaminated aquifers, and only four bacterial strains are known to respire it. Here, we obtained a novel Dehalobacter strain capable of transforming TCM to dichloromethane, which was denominated Dehalobacter sp. strain 8M. Besides TCM, strain 8M also completely transformed 1,1,2-trichloroethane to vinyl chloride and 1,2-dichloroethane. Quantitative PCR analysis for the 16S rRNA genes confirmed growth of Dehalobacter with TCM and 1,1,2-trichloroethane as electron acceptors. Carbon and chlorine isotope fractionation during TCM transformation was studied in cultured cells and in enzymatic assays with cell suspensions and crude protein extracts. TCM transformation in the three studied systems resulted in small but significant carbon (εC = -2.7 ± 0.1‰ for respiring cells, -3.1 ± 0.1‰ for cell suspensions, and - 4.1 ± 0.5‰ for crude protein extracts) and chlorine (εCl = -0.9 ± 0.1‰, -1.1 ± 0.1‰, and - 1.2 ± 0.2‰, respectively) isotope fractionation. A characteristic and consistent dual CCl isotope fractionation pattern was observed for the three systems (combined ΛC/Cl = 2.8 ± 0.3). This ΛC/Cl differed significantly from previously reported values for anaerobic dechlorination of TCM by the corrinoid cofactor vitamin B12 and other Dehalobacter strains. These findings widen our knowledge on the existence of different enzyme binding mechanisms underlying TCM-dechlorination within the genus Dehalobacter and demonstrates that dual isotope analysis could be a feasible tool to differentiate TCM degraders at field studies.
Keywords: Chemical Fractionation; Chloroform; 1,1,2-trichloroethane; Biodegradation, Environmental; biodegradace; Trichloromethane; RNA, Ribosomal, 16S; RNA ribozomální 16S; izotopy uhlíku; 2D-CSIA; Groundwater; Dehalobacter; chemická frakcionace; Carbon Isotopes; Organohalide respiration; chloroform; podzemní voda; Isotopic fractionation